Kulturtraegers and pristine nature. The vicissitudes of the Bialowieza Forest during the Great War (1914–1918) - Samuś, Paweł (Armia kontra natura, 2020)
Bialowieza Forest is an area of outstanding natural beauty, unique on a global scale. It covers a total area of approximately 1460 km², with 1/3 of the area in Poland and the remaining part in Belarus. Bialowieza Forest is one of the best-preserved, lowland, primeval forests. Bialowieza Forest is exceptional for the richness of it’s flora and fauna; it is home the area’s iconic species, the European bison (wisent). The whole area of Bialowieza Forest is protected and has been inscribed on UNESCO’s World Heritage List. In olden Times – Bialowieza Forest was under the rule of Ruthenian and then Lithuanian dukes, and over the next centuries – Polish kings. After the partitions of Poland, it was annexed by Russia. In 1888 it was added as appanage to the private tsar property and became a vast nature reserve and hunting grounds. During WW1, Bialowieza Forest came under German occupation (1915–1918). The occupation authorities called to life a Military Forest Commission, which over-exploited the Forest to cater for the needs of the army and German wartime economy. The occupiers caused huge devastation to the forest count, they felled approximately 5 million m³ worth of timber which was sent to Germany as raw material or processed in the newly-built industrial plants. The animals population of several thousand was decimated, with the European bison nearly hunter to extinction; out of 700 bisons roaming the Forest before the war, only a small fraction remained after the German occupation.